Life which reflects the epoch (to Prof. D.P. Chukhriyenko centennial) - Bereznitsky, Ya. S.; Kutovy, O. B.; Lyulko, I. V.; Reshetova, O. I.; Samarets, E. F. (Medicni Perspektivi, 2018)
Life which reflects the epoch (to Prof. D.P. Chukhriyenko centennial)